2001
DOI: 10.1046/j.0953-816x.2000.01451.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental pattern of expression of the alpha chemokine stromal cell‐derived factor 1 in the rat central nervous system

Abstract: Stromal cell-derived factor 1 (SDF-1) is an alpha-chemokine that stimulates migration of haematopoietic progenitor cells and development of the immune system. SDF-1 is also abundantly and selectively expressed in the developing and mature CNS, as we show here. At embryonic day 15, SDF-1 transcripts were detected in the germinal periventricular zone and in the deep layer of the forming cerebral cortex. At birth, granule cells in the cerebellum and glial cells of the olfactory bulb outer layer showed an SDF-1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(122 citation statements)
references
References 49 publications
10
110
2
Order By: Relevance
“…Our data demonstrate that activation of the SDF1␣-CXCR4 signaling pathway up-regulates the expression of GAD67 and the production of GABA in embryonic hippocampal neurons. In the developing hippocampus SDF1␣ may play an important role in regulating neurogenesis, gliogenesis, and the migration of dentate granule cells and synaptogenesis (26,58,59). Additional regulation of GABAergic neurons by SDF1␣ might function in the fine-tuning of synaptic circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrate that activation of the SDF1␣-CXCR4 signaling pathway up-regulates the expression of GAD67 and the production of GABA in embryonic hippocampal neurons. In the developing hippocampus SDF1␣ may play an important role in regulating neurogenesis, gliogenesis, and the migration of dentate granule cells and synaptogenesis (26,58,59). Additional regulation of GABAergic neurons by SDF1␣ might function in the fine-tuning of synaptic circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…The close juxtaposition of SDF-1 and CXCR4 in the adult DG suggests that CXCR4 may be an important regulator of adult neurogenesis in this part of the brain. Recent studies have demonstrated that SDF-1 is actually stored in neurotransmitter vesicles in DG neurons, including DG GABAergic interneurons such as Basket cells and granule cells (Tham et al, 2001). Both GABA and SDF-1 can be released in the DG and can regulate the functions of neural stem cells such as their proliferation (Bhattacharrya et al, unpublished observations).…”
Section: Adult Stem Cell Developmentmentioning
confidence: 99%
“…Furthermore, it has been reported that stromal-derived factor 1 (SDF-1) is a chemoattractant for cortical interneurons that is expressed not in the cortex itself but exclusively by meningeal cells (Stumm et al, 2003). However, several groups have reported SDF-1-expressing cells in the deeper aspect of the embryonic neocortex (Tham et al, 2001;Tissir et al, 2004), and this expression was associated with invading prospective interneurons (Daniel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…During corticogenesis, SDF-1 has been shown to be specifically expressed in the meninges above the MZ as well as in a deep domain (Tham et al, 2001;Tissir et al, 2004;Daniel et al, 2005). Stumm et al (2003) examined the effects of SDF-1 or CXCR4 knock-out on interneuron migration at a late stage of embryonic development (E18.5) and attributed the observed misrouting of CXCR4-or Reelin-expressing interneurons exclusively to the lack of chemoattraction by meningeal SDF-1.…”
Section: Sdf-1/cxcr4 Signaling In Interneuron Migrationmentioning
confidence: 99%